1993
DOI: 10.1177/095646249300400505
|View full text |Cite
|
Sign up to set email alerts
|

Anogenital Warts in Prepubertal Children; Sexual Abuse or Not?

Abstract: Forty-two prepubertal children presenting with anogenital (AG) warts (15 boys and 27 girls) were prospectively followed up (mean 15.9 months, SD 12.24). Most (73.8%) of these children had perianal condylomatous-type warts and 11 (26.2%) had concurrent non-genital (NG) warts. None had any other AG infections or sexually transmitted disease (STD). Twelve (28.6%) children acquired their AG warts by vertical transmission from an infected maternal birth canal, 3 (7.1%) by autoinoculation from common hand warts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 32 publications
3
22
1
2
Order By: Relevance
“…Anogenital warts Anogenital warts (AGW) are benign growths caused by more than 25 types of human papilloma virus (HPV), most frequently types 6, 11, 16, and 18, and are one of the most controversial issues in child sexual abuse literature [6,17,30,36,45,55]. They are considered to be the commonest sexually transmitted disease in adults [24].…”
Section: Mimickers Of Sexual Abusementioning
confidence: 99%
“…Anogenital warts Anogenital warts (AGW) are benign growths caused by more than 25 types of human papilloma virus (HPV), most frequently types 6, 11, 16, and 18, and are one of the most controversial issues in child sexual abuse literature [6,17,30,36,45,55]. They are considered to be the commonest sexually transmitted disease in adults [24].…”
Section: Mimickers Of Sexual Abusementioning
confidence: 99%
“…Study with 42 prepuberal children with anogenital warts found that 28.6% acquired HPV by vertical transmission, 7.1% resulted from self inoculation of warts located on the hands, and only 4.8% were associated with sexual abuse. The mode of transmission of HPV was considered inconclusive in 59.5% of the studied children, being not possible to relate the infection to sexual abuse 20 . The maternal history of vulvar condyloma or cervical squamous intraepithelial lesion at time of delivery was observed in 50.3% of children under nine years who presented different clinical forms of the disease 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Rogo KOet al 18 Obalek S et al 19 Handley J et al 20 Cason J et al 21 Smith EM et al 22 Puranen M et al 23 Frazier L 24 Kui LL et al 25 Myhre AK et al 26 Cheung PC et al 27 Simmons KJ et al 28 Marcoux D et al 29 Jones V et al Derksen DJ 31 Slaughter L et al 32 Handley J et al 20 Gutman LT et al 33 Siegfried E et al 10 Stevens-Simon et al 34 0Jesus LE et al 35 Kui LL et al 25 Sinclair KA et al 36 Jones Vet al 30 Wingood GM et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Başka bir çalışmada anoogenital siğili olan 42 prepubertal çocuğun ailesinde en az bir fertte % 23.8 oranında anogenital siğil, % 47 oranında ekstragenital siğil ve % 36.9 oranında baş-ka anogenital lezyon ya da cinsel yolla bulaşan hastalıklar (STD) saptanmıştır. Ayrıca % 62.2 oranında çocukların annesinde servikal intraepitelyal neoplazi (CIN) tespit edilmiştir [23]. Bizim çalışmamızda AGS'si bulunan 10 çocuğun annelerinden birinde AGS saptandı.…”
Section: Discussionunclassified